Management of chronic fissure in ano-lateral internal sphincterotomy versus 2% diltiazem gel local application: a prospective comparative study - Kulkarni, Srinivas B.; S., Naveen; Muddebihal, Uday (International Surgery Journal, 2023)
Background: Fissure-in-ano is one of the most common benign anorectal disorders often encountered in surgical outpatient department. Various pharmacological agents and surgical interventions have been tried in the management of fissure in ano. In this study we have compared medical management by topical diltiazem gel with established surgical procedure of lateral internal sphincterotomy (LIS) in the management of chronic anal fissure. Methods: A total of 50 patients with chronic fissure in ano involved in this prospective comparative study, between December 2020 to May 2022, at Rajarajeswari Medical College and Hospital, Bengaluru. Selected patients were put under two groups of 25 participants each, A (2% diltiazem group) and B (lateral internal sphincterotomy - LIS group) using simple randomization technique and were to receive treatment accordingly. Fissure healing and pain relief were recorded on presentation and during follow up visits. Results: The results were compared weekly for 4 weeks and monthly for 2 consecutive months. Fissure healing and pain relief were recorded. Conclusions: Both 2% diltiazem group and LIS group are equally effective and did not show any difference in pain relief or fissure healing with p value not significant (>0.05).